2017
DOI: 10.4103/ijem.ijem_548_16
|View full text |Cite
|
Sign up to set email alerts
|

An audit of insulin usage and insulin injection practices in a large Indian cohort

Abstract: Introduction:Insulin remains the cornerstone of therapy in a substantial number of patients with type 2 diabetes mellitus (T2DM). Inadequate knowledge regarding insulin usage is likely to influence its acceptance and adherence, and outcome of therapy, underscoring great need to investigate knowledge, attitude, and practice of insulin usage in patients with T2DM.Methodology:A cross-sectional registry-based retrospective study analyzed data collected from 748 respondents (male: 466, female: 282), mostly from hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 33 publications
3
39
1
1
Order By: Relevance
“…Thus, it can be hypothesized that rapid-acting insulin analogs with their improved pharmacokinetic actions might spare adipocytes from the lipogenic action as compared to conventional insulins. It is further supported by previous reports which suggest that faster absorption of insulin analogs reduces the stay of insulin in adipocytes and thereby provides a break from the local lipogenic action of insulin ( 33 , 34 ). Findings of present study also showed that as compared to multiple daily injections of rapid plus long-acting analogs, risk of lipohypertrophy further augmented to 4.6 times with conventional premixed insulins (twice daily).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, it can be hypothesized that rapid-acting insulin analogs with their improved pharmacokinetic actions might spare adipocytes from the lipogenic action as compared to conventional insulins. It is further supported by previous reports which suggest that faster absorption of insulin analogs reduces the stay of insulin in adipocytes and thereby provides a break from the local lipogenic action of insulin ( 33 , 34 ). Findings of present study also showed that as compared to multiple daily injections of rapid plus long-acting analogs, risk of lipohypertrophy further augmented to 4.6 times with conventional premixed insulins (twice daily).…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, despite the statistically insignificant ( p = 0.067) results, the pioneer European survey involving 1,002 patients accredited needle reuse as a contributor to lipohypertrophy ( 28 ). Furthermore, many subsequent studies unhesitatingly acknowledged the association of lipohypertrophy with needle reuse, only on the basis of univariate analysis ( 12 , 27 , 34 , 46 ). Vardar et al ( 26 ), Blanco et al ( 24 ), Ji et al ( 6 ), and Frid et al ( 25 ) did employ the multivariate analysis in their investigations.…”
Section: Discussionmentioning
confidence: 99%
“…For better bio-availability and to achieve glycemic control, correct insulin injecting techniques have to be followed by the patients. 4 The improper insulin injection techniques will also result in local adverse events such as Lipodystrophy which comprises of lipo hypertrophy (LH) and lipoatrophy (LA). These adverse events are caused by chronic reuse of needles and injections at the same site, improper or lack of rotation of sites.…”
mentioning
confidence: 99%
“…These highlight the need to understand the existing knowledge, attitude and practice regarding insulin usage technique among diabetic patients. 4 With this background, the present study was conducted at a tertiary care Basaveshwara hospital in Chitradurga, among diabetes patients on insulin treatment. The aim and objectives of the study were a) to assess the knowledge and insulin injection practices, b) to assess the risk factors of sharps injury among them.…”
mentioning
confidence: 99%
“…The use of ultrasound has been shown by some to improve diagnostic sensitivity both in terms of the frequency and the extent of detection [2]. A recent audit from India [3] reported a much lower prevalence at 12.5% of all insulin users although this was a retrospective collection of cases based only on clinical examination and could be an underestimate while another survey [4] on injection technique found that based on a physical examination by nurses, one in five diabetic patients on insulin had LH. Two recent studies [5,6] from India reported that more than 60% of the patients developed LH.…”
mentioning
confidence: 99%